The two-sector model of general equilibrium - Johnson, Harry G. (London : Allen and Unwin, 1971)
This important book presents a theory of general equilibrium and was the first to present in condensed form the construction of the two-sector model, its applications to the theory of distribution and public finance for income redistribution, and its conversion into a growth model. It assembles a body of analysis that was previously available only in scattered journal articles and a few textbook chapters.
Includes bibliographical references.
rpm 07/11/2017
Loans
Keywords: Economics